2021
DOI: 10.3390/membranes11080550
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Foreign Materials into Adherent Cells by Gold Nanoparticle-Mediated Photoporation

Abstract: Delivering extracellular materials into adherent cells presents several challenges. A homemade photoporation platform, mediated by gold nanoparticles (AuNPs), was constructed to find a suitable method for finding all adherent cells in this process with high delivery efficiency. The thermal dynamics of AuNPs could be monitored. Based on this system, 60 nm AuNPs were selected to be attached to cells for optimal photoporation. After irradiating the cells covered with AuNPs using a nanosecond pulse laser, fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Molecular weight of foreign substances is another factor. Several researches showed that the delivery efficiency decreased with increasing molecular weight of foreign materials (Xiong et al., 2016 ; Raes et al., 2019 ; Liu et al., 2020 ; Du et al., 2021 ). This phenomenon could attribute to diffusion velocity (Liu et al., 2020 ).…”
Section: The Factors Affecting the Delivery Efficiency Of Photoporationmentioning
confidence: 99%
“…Molecular weight of foreign substances is another factor. Several researches showed that the delivery efficiency decreased with increasing molecular weight of foreign materials (Xiong et al., 2016 ; Raes et al., 2019 ; Liu et al., 2020 ; Du et al., 2021 ). This phenomenon could attribute to diffusion velocity (Liu et al., 2020 ).…”
Section: The Factors Affecting the Delivery Efficiency Of Photoporationmentioning
confidence: 99%
“…23 So far, gold NP (AuNP)-sensitised photoporation has been studied extensively (Table S2†). 4,24–27 The majority of the studies used spherical AuNPs of size varying from 30–250 nm with a plasmonic peak located at ∼530 nm for intracellular delivery, and laser exposure was performed at varying wavelengths: 532 nm, 28,29 800 nm (ref. 26, 30 and 31) and 1064 nm.…”
Section: Introductionmentioning
confidence: 99%